Cardiac gene activation varies between young and adult cats and in the presence of hypertrophic cardiomyopathy. (20th December 2022) - Colpitts, Michelle E.; Caswell, Jeff L.; Monteith, Gabrielle; Joshua, Jessica; O'Sullivan, M. Lynne; Raheb, Shari; Fonfara, Sonja
Abstract: Little is known about the difference of myocardial gene transcription in young and adult cats and how transcription is further modified in cats with hypertrophic cardiomyopathy (HCM) and with left atrial (LA) thrombus formation. We hypothesized that selected factors for coagulation, endothelial activation, inflammation, and remodelling are modified with age and are activated in the hearts of cats with HCM. Left atrial and ventricular (LV) samples from 12 cats with HCM (seven without (HCMwoAT] and five with LA thrombi [HCMwAT]), and six young (YC) and six adult (AC) control cats without cardiac disease were investigated for relative expression of the following genes using quantitative polymerase chain reaction: von Willebrand factor, a disintegrin and metalloproteinase with a thrombospondin type 1 motif member 13, platelet activating factor, E- and P-selectin, intercellular and vascular adhesion molecules-1, ß2-integrin, vascular endothelial growth factor, interleukin-6 (IL-6), monocyte chemoattractant protein-1 (MCP-1), heat shock protein-70, and myocyte-specific enhancer factor 2C. Significant differences in gene activation were found between YC and AC, and YC and cats with HCM. Compared to AC, MCP-1 and IL-6 were significantly higher in cats with HCM. The presence of an LA thrombus was associated with higher IL-6 expression. These results illustrate the relevance of age and/or lifestyle on gene expression in the feline heart. The gene transcription pattern found in AC hearts might predispose cats to their characteristic cardiac remodelling processes and thrombus formation if disease occurs. It further supports the involvement of inflammation, but not coagulation and endothelial activation, in HCM. Highlights: Cardiac gene expression differs significantly between young and adult cats. Cardiac MCP-1 and IL-6 gene expression is higher in cats with HCM than adult controls. IL-6 expression is significantly higher in HCM hearts when a LA thrombus is present. Genes of coagulation and endothelial activation are not activated in cat HCM hearts.